Incremental steps toward incompatibility revealed by Arabidopsis epistatic interactions modulating salicylic acid pathway activation - Alcázar, Rubén; García, Ana V; Parker, Jane E; Reymond, Matthieu (Proceedings of the National Academy of Sciences - PNAS, 2009)
Plant growth is influenced by genetic factors and environmental cues. Genotype-by-environment interactions are governed by complex genetic epistatic networks that are subject to natural selection. Here we describe a novel epistatic interaction modulating growth in response to temperature common to 2 Arabidopsis recombinant inbred line (RIL) populations (Ler x Kas-2 and Ler x Kond). At 14 °C, lines with specific allele combinations at interacting loci (incompatible interactions) have severe growth defects. These lines exhibit deregulated cell death programs and enhanced disease resistance. At 20 °C, growth defects are suppressed, but a positive trait of enhanced resistance is retained. Mapping of 1 interacting QTL to a cluster of RPP1-like TIR-NB-LRR genes on chromosome 3 is consistent with our finding that environmentally conditioned epistasis depends on activation of the salicylic acid (SA) stress signaling pathway. The nature of the epistatic interaction conforms to the Dobzhansky-Muller model of genetic incompatibility with incomplete penetrance for reproductive isolation. Variation in fitness of different incompatible lines reveals the presence of additional modifiers in the genetic background. We propose that certain interacting loci lead to an optimal balance between growth and resistance to pathogens by modulating SA signaling under specific environments. This could allow the accumulation of additional incompatibilities before reaching complete reproductive isolation.